Urban Planning Support System Based on Three Dimensional GIS - Yu Kanhua (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In this study, the theory of technology analysis and decomposition of the 3-D (three dimensional) visualization of GIS (Geographic Information System) are analyzed, it divides the 3-D visualization of GIS into virtual reality technology, and it presents situation and development trend of 3-D visualization of GIS. It studies the urban model of 3-D data acquisition and processing, the classification of urban 3-D space information data and summarization of the characteristics of urban 3-D spatial data are made, and the three dimensional terrain data, building plane and building elevation data access, building surface texture are also analyzed. The high resolution satellite remote sensing data processing technology and aviation remote sensing data processing technology is studied, and the data acquisition and processing technology of airborne 3-D imager also are introduced This paper has solved the visualization of 3-D GIS data model and visual problem in the construction of the 3-D terrain and expression of choice of buildings, and it is to find suitable modeling route, and in order to provides a reference basis in realization of 3-D visualization of GIS. Visualization of 3-D model of the theory and method are studied in the urban construction, according to the 3D visualization in GIS and it proposed the two kinds of 3-D visualization model of GIS technology. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4110